Comparison of Design Response Spectra in SNI 1726:2012 and SNI 1726:2019 (International Journal of Innovative Research in Computer Science & Technology, 2023)
At the end of 2019, the Indonesian  National Standards Agency issued new regulations  regarding procedures for earthquake resistance planning in  building and non-building structures or SNI 1726:2019. The  existence of new regulations will certainly be one of the  issues that need attention regarding the safety of buildings  designed based on old regulations or SNI 1726:2012. This  paper aims to compare spectral acceleration designs based  on SNI 1726:2012 and SNI 1726:2019 for several cities in  Indonesia, namely Medan, Banda Aceh, Bengkulu, Padang,  Bandar Lampung, Yogyakarta, Surabaya, Palu, Ambon and  Jayapura.  The comparison results show that in hard (SC) and medium  (SD) soil conditions, almost all cities surveyed experienced  increased spectral acceleration values except for Medan and  Surabaya, where the values were the same. The increase in  the spectral acceleration value in hard (SC) and medium  (SD) soil conditions was very significant in the cities of  Palu, Jayapura, and Bengkulu. However, in soft soil (SE),  almost all survey cities experienced a decrease in spectral  acceleration, except for Medan and Surabaya, where the  spectral acceleration values were the same. Considering that  the results of spectral design comparisons in several cities  have increased, it is important to re-evaluate the existing  building structures.
Keywords: Earthquake; Spectrum Response; SNI 1726:2012; SNI 1726:2019